AN ANALYSIS OF PEMBAYUNS SPEECH ACTS IN SORONG SERAH CEREMONY OF SASAK MARRIAGE: A RITUALISTIC DISCOURSE STUDY - LN, YAQIN,; K, SEKEN,; W, SUARNAJAYA, (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This study investigated the Pembayuns speech acts in Sorong Serah ceremony of the Sasak marriage. As such, it examined the speech events that occurred within the ritual of the ceremony. It was designed as a descriptive qualitative research of the ethnography of communication type and employed observations and interviews as methods of data collection. Video recording and note-taking techniques were applied. The data analysis was affiliated with Wijanaâs (1996), Austinâs (1975) and Searleâs (1969) models of speech act theory and was done following Miles and Hubermanâs 1994) interactive model of data analysis. The findings of the study showed that the Pembayuns in Sorong Serah ceremony conveyed speech acts of certain types that can be categorized as direct speech acts, indirect speech acts, literal speech acts, nonliteral speech acts, direct literal speech acts, direct nonliteral speech acts, indirect literal speech acts, and indirect nonliteral speech acts. Among those eight forms of speech acts, indirect speech act was used most dominantly by the Pembayuns as it was seen as a politeness strategy. In relation to the force of utterances, it was found that the illocutionary acts used by the Pembayuns in Sorong Serah ceremony comprise a strategy that was oriented to face saving politeness (Brown & Levinson, 1987). All the five types of speech act were found to be used by the Pembayuns in Sorong Serah ceremony, namely: directive, commissive, expressive, representative, and declaration. These types of speech act were mainly concerned with values and wisdom related to politeness principles. Â  Keywords: Speech Acts, Strategy, Sorong Serah, Sasak Marriage.